Characteristics of guided modes in graphene-coated chiral nihility fibers - Muhammad Usman Shahid; Abdul Ghaffar; Majeed A. S. Alkanhal; Yasin Khan; Muhammad Amir Ali (PLoS ONE, 2025)
In this paper, guided modes in isotropic chiral nihility metamaterial fibers coated with graphene layers supported by conventional dielectric material are studied theoretically. Kubo formalism is applied to model the conductivity of single-layer graphene, and suitable boundary conditions are applied at the proposed waveguide structure. The dispersion equation for the chiral nihility fiber and the normalized cut-off frequency are derived. Characteristic curves for forward and backward modes, the effect of the graphene layer, the influence of the chirality parameter, and the energy flow distribution of several lower-order guided modes m=0,1,−1 in chiral nihility fibers are investigated briefly. It is found that the band gap between the curves of forward and backward modes may be tuned by radial distance, chiral strength, and chemical potential. By the addition of a graphene medium with chiral nihility, some novel properties of the chiral nihility fibers, such as anomalous dispersion and higher wave propagation, are examined. This graphene- and negative index material (NIM)-based structure makes it applicable for developing novel fiber devices, communication systems, and chiral sensing systems at the terahertz (THz) frequency.